2011
DOI: 10.1002/marc.201100557
|View full text |Cite
|
Sign up to set email alerts
|

Microspheres Consisting of Optically Active Helical Substituted Polyacetylenes: Preparation via Suspension Polymerization and Their Chiral Recognition/Release Properties

Abstract: Cross-linked microspheres consisting of optically active helical substituted polyacetylenes are reported. For preparing the microspheres, substituted polyacetylene copolymers with pendent polymerizable CC bonds are first prepared and then used as macromonomers to copolymerize with acrylates via suspension polymerization, providing cross-linked microspheres. The helical polymer segments render the microspheres with optical activity, whereas the acrylate-based polymers afford the swelling property. CD and UV-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…According to the strategy shown in Scheme , four kinds of MPs were prepared, namely non‐crosslinked and crosslinked MPs fabricated from poly1 (the polymer of M1) and poly2 (the polymer of M2), respectively. All of these MPs exhibited a yellow color, which is in accordance with earlier reports and originates from the helical substituted polyacetylenes …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…According to the strategy shown in Scheme , four kinds of MPs were prepared, namely non‐crosslinked and crosslinked MPs fabricated from poly1 (the polymer of M1) and poly2 (the polymer of M2), respectively. All of these MPs exhibited a yellow color, which is in accordance with earlier reports and originates from the helical substituted polyacetylenes …”
Section: Resultssupporting
confidence: 92%
“…The crosslinked poly1‐MPs were also expected to exhibit optical activity. In this case, the CD and UV‐vis spectra were measured as follows . A certain amount of the MPs were immersed in chloroform (or THF) for a given time to remove the soluble part, if any.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We prepared chiral polymer microspheres [20,21] and chiral polymer amphiphilic networks [22] in our previous studies, and all these materials with optical activity showed chiral recognition and enantioselective release ability. Based on these studies, we in the present study designed and prepared a new kind of chiral hydrogels by copolymerization of chiral hydrophilic monomer N-acryloyl-Lalanine (NAA) and hydrophobic monomer octadecyl acrylate (C18), with N,N 0 -methylenebisacrylamide (BIS) as crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%